Hubungan Pola Konsumsi Makanan Cepat Saji dan Frekuensi Pemesanan Makanan Online dengan Obesitas Sentral pada Siswa SMA di Yogyakarta: The Relationship between the Pattern of Fast Food Consumption and the Frequency of Online Food Ordering with Central Obesity in High School Students in Yogyakarta - Theresia Avila Early Nugraeni; Hildagardis Meliyani Erista Nai; Rijantono Franciscus Maria (Universitas Airlangga, 2023)
Background: Adolescents are at risk of experiencing health problems, one of which is central obesity. The factor that can affect central obesity is the consumption of fast food. Easy access to fast food via online food delivery during the COVID-19 pandemic. Objectives: Analyzed the relationship between the frequency of fast food consumption and the frequency of online food ordering with central obesity in high school students in Yogyakarta City. Methods: The study sample size was 219 people from 8 senior high schools. The sampling technique used multistage sampling. Collecting data on sample characteristics, frequency of fast food consumption, and online food ordering using Google Forms, abdominal circumference measurements were carried out directly using Medline. Data analysis used Chi Square and Fisher Exact test. Results: Most of the sample were women (60.3%), aged <17 years (64.4%), with income <IDR 1,000,000 (90.9%), and physical activity <30 minutes/day (79.9%). Frequency of consuming fast food frequently (≥3 times/week) (81.3%) and frequency of online food rarely ordering (<3 times/week) (71.7%). Bivariate analysis showed that there was no relationship between the frequency of fast food consumption and online food ordering with central obesity (p>0.05), and there was a relationship between fast food energy intake and central obesity (p<0.05). Multivariate analysis showed a relationship between fast food energy intake and central obesity (p<0.05). Conclusions: There was no relationship between the frequency of fast food consumption and online food ordering with central obesity in high school adolescents in Yogyakarta City.